Sophomore nursing students' perception of their Professional Behavior toward Rehabilitation patients: a cross-sectional study - Anat Amit-Aharon; Sigalit Warshawski (BMC, 2023)
Abstract Background Rehabilitation is considered one of the elements of universal health coverage, emphasizing its importance for every person in need throughout the life course. Nurses play a pivotal role in the rehabilitation team as they possess the competencies to help individuals manage health problems and maximize potential well-being. Yet, little is known regarding knowledge of this subject among nursing students, as well as regarding their attitudes, thoughts, and professional behavior. This study aimed to explore: (a) Sophomore students' attitudes, feelings, thoughts, and professional behavior toward rehabilitation patients; and (b) Differences in the research variables as affected by students' previous exposure to rehabilitation patients. Methods A cross-sectional survey design among sophomore nursing students. A questionnaire was distributed through a commercial internet survey provider (Qualtrics.com) before the beginning of a mandatory course on "nursing rehabilitation", introduced for the first time in 2022 in all Israeli universities. Students were divided into three groups according to their previous exposure to rehabilitation patients: no professional or personal previous exposure to rehabilitation patients; previous professional or personal exposure to rehabilitation patients; and previous exposure to rehabilitation patients both in one's professional and personal life. The study adhered to the STROBE guidelines. Results The sample consisted of 122 participants. Significant differences were found between the groups by their previous exposure to rehabilitation patients. Participants with no previous exposure to rehabilitation patients were found to have lower self-perceived capability to care for rehabilitation patients and more negative professional behavior toward rehabilitation patients and their families compared to the other two groups (H = 22.06, p = 0.006, H = 23.86, p = 0.03, respectively). No other statistical differences were observed between the groups. Conclusions The findings emphasize the importance of exposing students to the field of nursing rehabilitation and to the care of rehabilitation patients. Exposure to nursing rehabilitation specifically during one's studies, through theoretical learning and clinical experience, can promote positive attitudes, professional values, and positive professional behavior toward these patients and their families.